(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: The term thoracolumbar fracture essentially refers to the fact that the bone is broken in the thoracic (middle) or lumbar (lower back) region of the spine. The present prospective study has been objectively conducted to evaluate the clinical and radiological outcome of single stage subtotal corpectomy and circumferential reconstruction of unstable thoracolumbar burst fracture. Methods: This prospective study was carried out in GMC Jammu from October 2017 to December 2018. A total 20 patients with acute traumatic unstable burst fractures at thoracolumbar junctions were included in this prospective study who qualified the defined inclusion criteria.Results: The mean sagittal plane kyphosis pre operatively was 24.845.220 which reduced to 13.155.30at post-operative day 1. At final follow up, sagittal plane kyphosis was 15.105.650. The mean Anterior Body Compression was 33.646.79% which decreased to 22.3 % at post-operative day 1. At final follow up, mean ABC was 24.264.95%. VAS score reduced from mean value of 6.85 to 2.2 at final follow up which is slightly less compared to what others reported. Conclusion: The present study revealed that indirect decompression and posterior subtotal corpectomy and circumferential reconstruction fulfill all the aims of surgical treatment of fractures and fracture dislocations of thoracolumbar spine. We recommend longer follow up to assess the degree of correction of kyphosis and re-collapse and neural recovery with single stage posterior subtotal corpectomy and circumferential reconstruction